Emotion Regulation and Resilience as Predictors of Learning Motivation among Post-Flood University Students - Firmawati; Nur Sa’adah; Ikhwani; Riska Rahmadani (Journal of Educational, Health and Community Psychology, 2026)
Flooding in Bireuen Regency, Aceh (November 2025) disrupted the campus of Universitas Muhammadiyah Mahakarya Aceh (UMMAH), a university fewer than four years old. This study examined whether cognitive reappraisal, expressive suppression, and resilience predicted academic motivation approximately one month after the flood. Using a correlational-predictive design, data were collected from 117 UMMAH students with confirmed flood exposure (response rate: 75.0%) via the Emotion Regulation Questionnaire (ERQ), Connor-Davidson Resilience Scale (CD-RISC), and Motivated Strategies for Learning Questionnaire (MSLQ). Simple regression confirmed all three predictors were individually significant. Multiple regression revealed that cognitive reappraisal (β = .36, EC = 20.9%) and resilience (β = .49, EC = 31.8%) were significant unique predictors, while expressive suppression contributed no unique variance (β = .07, p = .350). Together, the three variables explained 54.1% of variance in post-flood academic motivation (R² = .541). Findings supported targeted reappraisal and resilience-building programmes in disaster-affected universities.